Main features of a constructivist landscape theory and its consequences for spatial planning - Kühne, Olaf (Raumforschung und Raumordnung | Spatial Research and Planning, 2009)
The paper is based on the social constructivist landscape theory. In this setting, landscape is not constituted as a physical object but as a social construct that uses physical objects. Consequently, landscape can be described as a hybrid based on individual and social conceptions which includes also physical objects. Another dimension of the hybrid is the fact that landscape has cultural references as well as natural ones. Concerning the practice with landscape in the spatial planning these remarks imply that landscape could not reduced to its physical objects. It rather should be thought also as a social and individual construct. In this context has to be considered that landscape is barely able to be planned because it is usually an unintended side-effect of social development. Furthermore the integration of the needs of minors in power concerning the practice with landscape is demanded.